Porous ceramic laminate and separation membrane

JP2025022449APending Publication Date: 2025-02-14SUMITOMO CHEM CO LTD

Patent Information

Application Number
JP2023127032
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

【0010】 本発明によれば、第1の多孔質セラミックス層とその上に積層された他の多孔質セラミックス層との間で剥離強度が向上した多孔質セラミックス積層体を提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025022449000001_ABST
    Figure 2025022449000001_ABST
Patent Text Reader

Abstract

To provide a porous ceramic laminate in which two or more layers are laminated and peeling at a lamination interface is suppressed.SOLUTION: There is provided a porous ceramic laminate in which one or more other porous ceramic layers are laminated on a first porous ceramic layer constituted by ceramic beams and pores, wherein the number of branch points of the pores is 1.0×106 or more per 1 μm3 of total volume of the ceramic beams and pores. Volume of protruding valleys on a surface of the first porous ceramic layer is preferably more than 0.56 ml / m2 as determined according to ISO 25178.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a porous ceramic laminate and a separation membrane. [Background technology]

[0002] Porous ceramic bodies are used in various fields as membranes having functions such as separation, concentration, or filtration of fluids, such as gases or liquids, such as microfiltration membranes, ultrafiltration membranes, nanofiltration membranes, reverse osmosis membranes, ion exchange membranes, and gas separation membranes.

[0003] It is important that porous ceramic bodies suitable for use in the fields described above can fully perform functions such as separation while allowing fluids to flow easily through the porous ceramic body. For this reason, they are usually composed of a laminate of two or more layers including a functional layer with a small pore diameter and a support layer with a large pore diameter that supports the functional layer.

[0004] Patent Document 1 discloses a ceramic filter formed by laminating one or more layers of a porous ceramic membrane having an average pore diameter smaller than that of an alumina-based porous body on the surface of the alumina-based porous body as a base material. Patent Document 1 describes that the corrosion resistance against alkaline and acidic solutions can be improved by adjusting the porosity and average pore diameter of the alumina-based porous body as a base material and by containing a predetermined amount of at least one metal oxide selected from the group consisting of titanium, manganese, and copper relative to the alumina.

[0005] Similarly to Patent Document 1, Patent Document 2 discloses a ceramic filter formed by laminating one or more layers of a porous ceramic membrane having an average pore diameter smaller than that of an alumina porous body on the surface of the alumina porous body as a substrate. Patent Document 2 describes that the alumina porous body as a substrate has a high initial strength and improved corrosion resistance to alkaline and acidic solutions by adjusting the porosity and average pore diameter and containing a predetermined amount of titanium oxide and at least one element selected from the group consisting of copper, manganese, calcium, and strontium. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2010-228946 A [Patent Document 2] JP 2010-228948 A Summary of the Invention [Problem to be solved by the invention]

[0007] In a laminate in which two or more types of layers are laminated, if the bonding at the interface of the layers is not strong when a load is applied to the laminate, peeling will occur at the interface of the layers.

[0008] The aforementioned Patent Documents 1 and 2 also disclose a laminate as a structure of a separation membrane, but do not consider peeling at the lamination interface. Therefore, an object of the present invention is to provide a porous ceramic laminate in which two or more types of layers are laminated, in which peeling at the lamination interface is suppressed. [Means for solving the problem]

[0009] The present invention, which has achieved the above object, is as follows. [1] A porous ceramic laminate in which one or more other porous ceramic layers are laminated on a first porous ceramic layer composed of ceramic trabeculae and pores, The number of branching points of the pores is within 1 μm of the total volume of the ceramic trabeculae and the pores. 3 1.0×10 per 6 The porous ceramic laminate has at least one porous ceramic layer. [2] The volume of the protruding valleys on the surface of the first porous ceramic layer, as determined in accordance with ISO 25178, is 0.56 ml / m 2 The porous ceramic laminate according to [1], [3] The porous ceramic laminate according to [1] or [2], wherein the other porous ceramic layer is composed of two or more layers. [4] The other porous ceramic layer is a layer containing small particles having a circle-equivalent particle diameter of less than 1 μm in a cross section parallel to the stacking direction of the laminate, A porous ceramic laminate according to any one of [1] to [3], wherein the small particles and large particles having a circle equivalent particle diameter of 2 μm to 25 μm are present on the surface of the first porous ceramic layer facing the other porous ceramic layer. [5] The porous ceramic laminate according to [4], wherein the layer containing the small particles is composed of an outer layer containing the small particles and not containing the large particles, and an intermediate layer containing both the small particles and the large particles. [6] The average circle equivalent particle diameter of the large particles present on the surface of the first porous ceramic layer is equal to or smaller than the average pore diameter D of the first porous ceramic layer. 50 The porous ceramic laminate according to [4] or [5], wherein the porous ceramic laminate has a surface area of ​​0.3 times or more. [7] The porous ceramic laminate according to any one of [4] to [6], wherein the large particles and the small particles are both made of an inorganic oxide. [8] The porous ceramic laminate according to any one of [1] to [7], which is in a tubular or monolithic shape. [9] A separation membrane comprising the porous ceramic laminate according to any one of [1] to [8]. Effect of the Invention

[0010] According to the present invention, it is possible to provide a porous ceramic laminate having improved peel strength between a first porous ceramic layer and another porous ceramic layer laminated thereon. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a schematic diagram showing the pores of the first porous ceramic layer. [Diagram 2] FIG. 2 is a schematic diagram showing an example of an embodiment of the present invention. [Diagram 3] FIG. 3 is a schematic diagram showing another embodiment of the present invention. [Figure 4] FIG. 4 is a photograph, substituted for a drawing, showing a cross-sectional SEM image of a porous ceramic laminate of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention relates to a porous ceramic laminate in which one or more other porous ceramic layers are laminated on a first porous ceramic layer composed of ceramic trabeculae and pores, and the number of branch points of the pores is within 1 μm of the total volume of the ceramic trabeculae and the pores. 3 per 1 μm of the first porous ceramic layer 3 per) 1.0 x 10 6 1 or more.

[0013] (1) First porous ceramic layer The first porous ceramic layer is composed of ceramic trabeculae and pores (voids). The pores usually extend three-dimensionally in the porous ceramic layer. Pores extending three-dimensionally can also be said to mean that the pores are shapeless or not linear. Figure 1 is a schematic diagram of the pores in the first porous ceramic layer, and the locations indicated by 11 are branching points. The number of branching points, which can be determined by performing a three-dimensional quantitative analysis of the pores in the first porous ceramic layer using the method described below, is calculated as the number of branching points per 1 μm of the first porous ceramic layer. 3 1.0×10 per6 The number of branch points is 1 μm or more, and the greater the number of branch points, the greater the unevenness of the surface of the first porous ceramic layer, and the stronger the bonding strength with other porous ceramic layers laminated on the first porous ceramic layer. 3 1.1×10 per 6 10 or more, and more preferably 1.2×10 6 More preferably, it is 1.5×10 6 The upper limit is not particularly limited, but is, for example, 2.5 × 10 6 It may be one piece.

[0014] The number of branching points in the first porous ceramic layer is found by binarizing a three-dimensional image of the first porous ceramic layer to distinguish the pores, and then performing a thinning process on the pores. A more detailed measurement procedure is as shown in the examples described later, and first, the first porous ceramic layer is observed three-dimensionally by X-ray CT (Computed Tomography) to obtain a 3D image. The 3D image is binarized using quantitative analysis software TRI / 3D-BON-FCS (manufactured by Ratoc Systems Engineering) to distinguish the trabecular bone portion and the pores, and the structure of the 3D image is analyzed by 3D cancellous bone measurement using the bone measurement option, and the number of pore branches and the total volume of the ceramic trabeculae and pores are calculated to obtain the number of branching points in the first porous ceramic layer per μm 3 The number of branching points is preferably measured within a range of about 600 μm in the depth direction from the surface of the first porous ceramic layer on the side where another porous ceramic is laminated.

[0015] In addition, it is preferable that the volume of the protruding valleys on the surface of the first porous ceramic layer, as determined in accordance with ISO 25178, is large, since the volume of the depressions on the surface is large. Specifically, it is preferable that the volume of the protruding valleys on the surface of the first porous ceramic layer is large. 2 More preferably, it is greater than 0.60 ml / m 2 More preferably, it is 0.70 ml / m or more. 2The upper limit is not particularly limited, but is, for example, 1.5 ml / m 2 may be also possible.

[0016] It is also preferable that the surface of the first porous ceramic layer satisfies the above-mentioned requirement for the volume of the protruding valleys and further has a small volume of the protruding peaks as determined in accordance with ISO25178, specifically, 0.25 ml / m 2 Preferably, it is less than 0.22 ml / m 2 More preferably, it is 0.19 ml / m or less. 2 The lower limit is not particularly limited, but is, for example, 0.05 ml / m 2 may be also possible.

[0017] The average pore diameter D50 of the first porous ceramic layer is measured by a three-dimensional analysis method (similar to the measurement of the number of branch points described above, a structural analysis of a 3D image is performed using the quantitative analysis software described above, and the average value of the length between the connecting points Nd of the voids and the width of the voids is obtained), and the value is, for example, 6.0 μm or more, more preferably 10.0 μm or more, and even more preferably more than 13.0 μm, and may be 20 μm or less, or 18 μm or less.

[0018] The first porous ceramic layer preferably contains an inorganic oxide, for example, Li2O, BeO, B2O3, Na2O, MgO, Al2O3, SiO2, K2O, CaO, ScO2, TiO2, V2O5, Cr2O3, ZnO, Ga2O3, GeO2, As2O5, Rb2O, SrO, Y2O3, ZrO2, Nb2O5, Ag2O, CdO, In2O3, SnO2, Sb2O5, TeO2, Cs2O, BaO, La2O3, Ta2O5, WO3, HgO, Tl2O, PbO, PbO2, and ThO2. The first porous layer more preferably contains Al2O3 and one or more metal oxides other than Al2O3. The one or more metal oxides other than Al2O3 that are preferably contained in the first porous layer can be arbitrarily selected from the metal oxides exemplified above, and it is particularly preferable that the first porous layer is a glass containing Al2O3 and SiO2. Note that the term "metal" in this specification is used to include semimetals such as Si.

[0019] The shape of the first porous ceramic layer is not particularly limited, and may be, for example, a plate shape, a tube shape, or a monolith shape, and is particularly preferably a tube shape or a monolith shape. In any of the above shapes, the corners may be rounded. The monolith shape means a columnar (cylinder, square column, elliptical column, etc.) shape having a plurality of holes (preferably a cylindrical shape) penetrating in the axial direction. When the first porous ceramic layer is tubular, the other porous ceramic layer is preferably formed only on the inner peripheral surface, only on the outer peripheral surface, or both the inner peripheral surface and the outer peripheral surface of the tube, more preferably formed only on the inner peripheral surface or only on the outer peripheral surface, and even more preferably formed only on the inner peripheral surface. When the first porous ceramic layer is monolithic, the other porous ceramic layer is preferably formed only on the inner surface of each through hole of the monolithic shape.

[0020] The porous ceramic laminate of the present invention comprises a first porous ceramic layer and at least one other porous ceramic layer laminated on the first porous ceramic layer, and has the same shape as the first porous ceramic layer.

[0021] The thickness (average value) of the first porous ceramic layer is preferably 400 μm to 8000 μm. When the first porous ceramic layer is monolithic, the thickness may be the average value of the closest distance between adjacent through holes on a plane perpendicular to the long axis. The length of the first porous ceramic layer in the longitudinal direction is, for example, 50 mm to 5000 mm, and preferably 500 mm to 3000 mm. The length in the longitudinal direction means, for example, the length of the long side in the case of a plate shape, and the length in the long axis direction in the case of a tube shape or monolith shape. When the first porous ceramic layer is tubular, the outer diameter of the first porous ceramic layer is, for example, 5 mm to 20 mm, and the inner diameter of the tube is, for example, 1 mm to 15 mm. When the first porous ceramic layer is monolithic, that is, when it has two or more tubes, the outer diameter of the first porous ceramic layer is, for example, 5 mm to 100 mm, and the inner diameter of each tube is, for example, 0.1 mm to 10 mm.

[0022] (2) Another porous ceramic layer The porous ceramic laminate of the present invention has one or more other porous ceramic layers laminated on the above-mentioned first porous ceramic layer, and may be a laminate composed of a first porous ceramic layer 21 and one other porous ceramic layer 22 as shown in Fig. 2, or a laminate composed of a first porous ceramic layer 31 and other porous ceramic layers 32, 33 (two layers) as shown in Fig. 3, or a laminate in which one or more porous ceramic layers are further laminated on the porous ceramic layer 33 in Fig. 3. It is preferable that the porous ceramic laminate of the present invention is composed of two or more other porous ceramic layers.

[0023] In the porous ceramic laminate of the present invention, it is preferable that the other porous ceramic layer is a layer containing small particles having a circle-equivalent particle diameter of less than 1 μm in a cross section parallel to the stacking direction of the laminate, and the small particles and large particles having a circle-equivalent particle diameter of 2 μm to 25 μm are present on the surface of the first porous ceramic layer. The porous ceramic laminate of the present invention that satisfies such requirements is hereinafter referred to as a laminate P. The configuration of the laminate P is advantageous for improving the peel strength between the first porous ceramic layer and the other porous ceramic layer stacked thereon. The lower limit of the circle-equivalent particle diameter of the small particles may be about 0.05 μm. The cross section parallel to the stacking direction of the laminate can be, for example, a cross section perpendicular to the longitudinal direction of the laminate (for example, the axial direction when the outer shape of the laminate is a columnar shape such as a cylinder, a rectangular cylinder, or an elliptical cylinder).

[0024] In the laminate P, the layer containing small particles is preferably composed of an outer layer containing the small particles but not the large particles, and an intermediate layer containing both the small particles and the large particles. The thickness of the intermediate layer can be, for example, 3 μm to 100 μm, and is preferably 3 μm to 60 μm. The thickness of the outer layer is, for example, 5 μm to 100 μm, and more preferably 20 μm to 80 μm. When the layer containing small particles includes an intermediate layer and an outer layer, one or more other layers may be further laminated between the intermediate layer and the outer layer, or on the outer layer.

[0025] For the intermediate layer, in a cross section parallel to the stacking direction of the laminate, straight lines are drawn from any five points on the surface of the first porous layer (the surface on the intermediate layer side) in the stacking direction (for example, the thickness direction if the laminate is in the form of a plate, or the radial direction of the through hole if the laminate is in the form of a tube or monolith having a cylindrical through hole and the intermediate layer is formed on the inner surface of the through hole), and the length of the line segments to the point where they intersect with the interface between the intermediate layer and the outer layer is measured, and the average value of the five line segments can be regarded as the thickness of the intermediate layer. For the outer layer, straight lines can be drawn in the stacking direction from any five points on the interface between the intermediate layer and the outer layer, and the length of the line segments to the points where they intersect with the surface of the outer layer can be measured, and the average value of the five line segments can be used as the thickness of the outer layer.

[0026] The surface of the porous ceramic laminate of the present invention opposite the first porous ceramic layer is measured by mercury intrusion porosimetry, and the cumulative 50% equivalent diameter calculated from a graph with the pore diameter on the horizontal axis and the cumulative log differential pore volume on the vertical axis is, for example, 0.01 μm to 0.5 μm.

[0027] The average circle-equivalent particle diameter of the large particles present on the surface of the first porous ceramic layer is equal to or smaller than the average pore diameter D of the first porous ceramic layer. 50 It is preferable that the average value of the circle-equivalent particle diameter of the large particles is 0.3 times or more, more preferably 0.7 times or more, and further preferably 0.8 times or more. By adopting such a configuration, it is easy to form another porous ceramic layer on the first porous ceramic layer. 50 The average circle-equivalent particle diameter of the large particles present on the surface of the first porous ceramic layer may be determined by arbitrarily selecting 20 large particles in a section parallel to the lamination direction of the laminate between lines X1 and X0 below, and calculating the average circle-equivalent particle diameter of the large particles. Note that the large particles in the section between lines X1 and X0 below mean particles at least partially present in the section between lines X1 and X0, and if the target large particles have a portion protruding from lines X1 and X0, the circle-equivalent particle diameter of the entire large particle including the protruding portion is measured. Line X1: A line that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer. Straight line X0: A line parallel to the straight line X1 and spaced 10 μm apart in the direction toward the inside of the first porous ceramic layer

[0028] The other porous ceramic layer is preferably composed of an inorganic oxide, that is, both the large particles and the small particles in the preferred embodiment are preferably inorganic oxides. Examples of inorganic oxides include the metal oxides listed as the preferred embodiment of the first porous ceramic layer. In particular, both the large particles and the small particles are preferably Al2O3. As Al2O3, commercially available α-alumina can be used, and there is no particular restriction. For the large particles, AA-10, AA-5, etc. manufactured by Sumitomo Chemical Co., Ltd. can be used, and for the small particles, AKP-3000, AKP-20, etc. manufactured by Sumitomo Chemical Co., Ltd. can be used.

[0029] (3) Manufacturing method of ceramic laminate (3-1) Manufacturing method of the first porous ceramic layer The first porous ceramic layer is formed such that the number of branching points of the pores measured as described above is 1 μm 3 1.0×10 per 6 One or more commercially available ceramic substrates may be used, or the first porous ceramic layer may be produced by the following method: The first porous ceramic layer can be produced by molding and firing a raw material mixture containing an inorganic raw material powder, which is at least one of an aluminum source powder, a silicon source powder, and a magnesium source powder, a pore-forming agent, a binder, and the like.

[0030] Examples of the aluminum source include alumina, kaolin (Al2Si2O5(OH)4), aluminum hydroxide, aluminum salts, aluminum alkoxides, aluminum titanate, metallic aluminum, etc. As the aluminum source, only one type may be used, or two or more types may be used in combination. The crystal type of alumina includes γ type, δ type, θ type, α type, etc., and may be amorphous. A mixture of these may also be used. Among them, α type alumina is preferably used. Examples of the crystal form of aluminum hydroxide include gibbsite type, bayerite type, norostrantite type, boehmite type, pseudoboehmite type, etc., and may be amorphous. Examples of amorphous aluminum hydroxide include aluminum hydrolysates obtained by hydrolyzing aqueous solutions of water-soluble aluminum compounds such as aluminum salts and aluminum alkoxides. The aluminum salt may be an inorganic salt with an inorganic acid, or an organic salt with an organic acid.Specific examples of the aluminum inorganic salt include aluminum nitrates such as aluminum nitrate and ammonium aluminum nitrate, and aluminum carbonates such as ammonium aluminum carbonate.Specific examples of the aluminum organic salt include aluminum oxalate, aluminum acetate, aluminum stearate, aluminum lactate, and aluminum laurate.

[0031] Silicon sources include silicon oxide (quartz, amorphous silica), talc (Mg3Si4O 10 (OH)2), kaolin (Al2Si2O5(OH)4), etc. Talc also functions as a magnesium source, and kaolin also functions as an aluminum source. Other silicon sources include silicic acid, silicon carbide, silicon nitride, silicon sulfide, silicon tetrachloride, silicon acetate, sodium silicate, sodium orthosilicate, glass frit, etc. As the silicon source, only one type may be used, or two or more types may be used in combination.

[0032] Magnesium sources include magnesia spinel, magnesium oxide, and talc (Mg3Si4O 10 (OH)2), magnesium salts, magnesium alkoxides, magnesium hydroxide, magnesium nitride, metallic magnesium, etc. As the magnesium source, only one type may be used, or two or more types may be used in combination. Specific examples of magnesium salts include magnesium chloride, magnesium perchlorate, magnesium phosphate, magnesium pyrophosphate, magnesium oxalate, magnesium nitrate, magnesium carbonate, magnesium acetate, magnesium sulfate, magnesium citrate, magnesium lactate, magnesium stearate, magnesium salicylate, magnesium myristate, magnesium gluconate, magnesium dimethacrylate, and magnesium benzoate.

[0033] Examples of the pore-forming agent include carbon materials such as graphite; resins such as polyethylene, polypropylene, and polymethyl methacrylate; plant materials such as starch, nut shells, walnut shells, and corn; ice; and dry ice.

[0034] Examples of binders include celluloses such as methyl cellulose, carboxymethyl cellulose, hydroxyalkyl methyl cellulose, and sodium carboxymethyl cellulose; alcohols such as polyvinyl alcohol; salts such as lignin sulfonate; and waxes such as paraffin wax and microcrystalline wax.

[0035] In the molding step, a molding device such as a commonly used uniaxial press or extrusion molding machine may be used to mold the mixture into the desired shape. In order to reduce the number of branch points, the constituent particles (aluminum source powder, silicon source powder, or magnesium source powder) should be made larger and / or a pore-forming agent that forms relatively large pores should be used, whereas in order to increase the number of branch points, the constituent particles should be made smaller and / or a pore-forming agent that forms relatively small pores should be used and mixed uniformly.

[0036] In the firing step, before firing the molded body, a calcination (degreasing) may be performed to remove binders and the like contained in the molded body (raw material). In firing the molded body, the firing temperature is usually 1300°C or higher, preferably 1400°C or higher. The firing temperature is usually 1550°C or lower, preferably 1500°C or lower. The heating rate is not particularly limited, but is usually 1°C / hour to 500°C / hour. When the pore-forming agent is an organic powder and a carbon powder, it is preferable to perform the firing in an oxygen-containing atmosphere. The firing is usually performed using a normal firing furnace such as a tubular electric furnace, a box-type electric furnace, a tunnel furnace, a microwave heating furnace, a rotary furnace, a roller hearth furnace, or a gas firing furnace. The firing time may be sufficient to transition the inorganic raw material powder to cordierite-based crystals, and varies depending on the amount of raw material, the type of the firing furnace, the firing temperature, the firing atmosphere, and the like, but is usually 5 hours to 24 hours.

[0037] (3-2) Manufacturing method of porous ceramic laminate The porous ceramic laminate of the present invention can be manufactured by preparing a slurry containing an inorganic oxide, applying the slurry to the lower layer as the substrate, heat-treating it, and repeating the slurry application and heat-treating as necessary. The composition of the inorganic oxide can be referred to the above description of the large particles and small particles, and when the inorganic oxide contains Al2O3, commercially available α-alumina can be used as Al2O3, for example, AKP-3000, AKP-20, AA-10, AA-5, etc. manufactured by Sumitomo Chemical Co., Ltd. The volume-based cumulative 50% equivalent diameter of the inorganic oxide is, for example, about 0.05 μm to 20 μm, preferably 0.1 μm to 15 μm. The concentration of the inorganic oxide in the slurry is, for example, 5 mass% to 15 mass%.

[0038] The slurry containing an inorganic oxide preferably contains a dispersant, a thickener and a solvent in addition to the inorganic oxide.

[0039] The dispersant can suppress the aggregation of inorganic oxide particles in the slurry. The dispersant may be any of cationic surfactants, anionic surfactants, nonionic surfactants, and amphoteric surfactants. Among them, anionic surfactants such as polycarboxylate ammonium salts and polycarboxylate amine salts are preferred, and SN Dispersant 5020, SN Dispersant 5023, SN Dispersant 5027, SN Dispersant 5468, Noparfa D-6010, Nopcol 5200, Nopcosant RFA, Nopcosperse 6100, and Nopcosperse 6150 manufactured by San Nopco can be used. The concentration of the dispersant in the slurry (in terms of active ingredient) is, for example, 0.1% by mass or more and 3% by mass or less, and preferably 0.3% by mass or more and 2% by mass or less. The concentration of the dispersant in the slurry (in terms of active ingredient) is, for example, 0.01% by mass or more and 10% by mass or less with respect to 100% by mass of inorganic particles in the slurry.

[0040] Examples of the thickener include methyl cellulose, hydroxyethyl methyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, polyalkylene oxide, polyvinyl alcohol, sodium polyacrylate, polyvinylpyrrolidone, polyacrylamide, polydimethylaminoethyl methacrylate, etc., and hydroxypropyl methyl cellulose is particularly preferred. The amount of the thickener to be added can be appropriately adjusted depending on the target slurry viscosity.

[0041] The solvent may be water or an organic solvent.

[0042] Methods for applying the slurry to the substrate include dip coating, spray coating, roll coating, bar coating, spin coating, slit coating, ball injection, brush coating, etc. After the slurry is applied, heat treatment (firing) is performed. The heat treatment temperature is, for example, 1000°C or higher and 1500°C or lower, and the heat treatment time is, for example, 1 hour or higher and 8 hours or lower.

[0043] In particular, when the first porous ceramic layer is tubular or monolithic, and the laminate of the present invention is the laminate P described above, the laminate of the present invention may be manufactured by a method of forming the laminate on the inner surface of the tube or monolith using a jig (hereinafter, referred to as a ball injection method). This will be explained in more detail below.

[0044] In the ball injection method, a slurry containing particles X1 having a volume-based cumulative 50% equivalent diameter of 1 μm to 20 μm and particles X2 having a volume-based cumulative 50% equivalent diameter of 0.05 μm or more and less than 1 μm may be applied onto the first porous ceramic layer by a dipping method, a spray coating method, a spin coating method, a bar coating method, or the like, and then dried. Alternatively, after the drying, a slurry containing particles Y1 having a volume-based cumulative 50% equivalent diameter of 0.05 μm or more and less than 1 μm (preferably 0.1 μm or more and less than 1 μm) but not containing particles having a volume-based cumulative 50% equivalent diameter of 1 μm to 20 μm (preferably 1 μm to 15 μm) may be applied, dried, and further heat-treated as necessary to produce the porous ceramic layer.

[0045] The ball injection method is a method for producing a ceramic porous laminate by forming a ceramic porous layer on the inner surface of a tubular or monolithic first porous ceramic layer, i.e., a first porous ceramic layer having one or more tubes (hereinafter sometimes referred to as a substrate), and is a production method comprising a slurry liquid supplying step (1) for supplying a slurry liquid containing particles to the inside of the tube, and a coating layer forming step (2) for passing a jig through the tube to form a coating layer of the slurry liquid on the inner surface of the tube while supplying the slurry liquid or after supplying the slurry liquid.

[0046] The slurry liquid containing particles is a raw material for a ceramic porous layer formed on a substrate. In a preferred embodiment of the ball injection method, a slurry liquid X supplying step (1X) of supplying a slurry liquid X containing particles X1 having a cumulative 50% equivalent diameter on a volume basis of 1 μm to 20 μm (preferably 1 μm to 15 μm) to the inside of a substrate having one or more tubes, a coating layer forming step (2X) of the slurry liquid X, and a drying step (3X) are performed to form a coating layer containing particles X1 on the inner surface of the tube, and further, a slurry liquid Y supplying step (1Y) of supplying a slurry liquid Y containing particles Y1 having a cumulative 50% equivalent diameter on a volume basis of 0.05 μm or more to less than 1 μm (preferably 0.1 μm or more to less than 1 μm), a coating layer forming step (2Y) of the slurry liquid Y, and a drying step (3Y) are performed to form a coating layer containing particles Y1 on the inside of the tube on which the coating layer containing particles X1 has been formed. A heat treatment step (4X) may be further performed after the drying step (3X), or a heat treatment step (4Y) may be further performed after the drying step (3Y). In addition to the X1, the slurry liquid X also preferably contains particles X2 having a volume-based cumulative 50% equivalent diameter of 0.05 μm or more and less than 1 μm (preferably 0.1 μm or more and less than 1 μm). The particles X1 having a volume-based cumulative 50% equivalent diameter of 1 μm to 20 μm (preferably 1 μm to 15 μm) correspond to the above-mentioned large particles, and the particles X2 and Y1 having a volume-based cumulative 50% equivalent diameter of 0.05 μm or more and less than 1 μm (preferably 0.1 μm or more and less than 1 μm) correspond to the above-mentioned small particles.

[0047] In the ball injection method, the slurry liquid preferably contains the above-mentioned dispersant, thickener and solvent in addition to the particles, and the types, concentrations and other preferred ranges can all be referenced.

[0048] When supplying the slurry liquid to the substrate and when passing the jig through the pipe, it is preferable to arrange the substrate so that the axial direction thereof is vertical.

[0049] In the slurry liquid supplying step (1), the slurry liquid may be supplied from either end of the substrate, but when the substrate is arranged so that its axial direction is vertical, it is preferable to supply the slurry liquid from the lower end of the substrate. The supply of the slurry liquid may be carried out by injecting the slurry liquid from the end of the substrate, or by masking the substrate end face other than the hole of the tube and the substrate side surface and immersing the substrate in the slurry liquid, but it is preferable to supply the slurry liquid by injection from the end of the substrate (particularly one end).

[0050] In the coating layer forming step (2) of the slurry liquid, by using a jig, the excess of the slurry liquid supplied to the inner tube surface of the substrate can be discharged, and the slurry liquid can be uniformly applied to the inner tube surface of the substrate. The jig may be passed through the tube after the slurry liquid is supplied, or may be passed through the tube while the slurry liquid is being supplied. It is preferable to supply the slurry liquid to the inside of the tube and pass the jig after the slurry liquid is supplied, and it is more preferable to supply the slurry liquid to the inside of the tube by injection and pass the jig after the slurry liquid is injected.

[0051] The direction of supply of the slurry liquid and the direction of passing the jig may be the same or different. When the substrate is arranged so that the axial direction is vertical, it is preferable to pass the jig from the upper end after the slurry liquid is supplied from the end of the substrate to the inner tube surface of the substrate.

[0052] The method of passing the jig through the tube of the substrate includes (i) flowing a fluid other than the slurry liquid from the rear of the jig in the direction of the jig's movement, (ii) sucking the slurry liquid from the direction of the jig's advancement, or (iii) performing both of these. In addition, when the substrate is arranged so that the axial direction is vertical, (iv) the jig may be passed through by dropping it from the upper end of the substrate under its own weight. The fluid includes a gas such as air. The method of moving the jig is particularly preferably (i) to (iii), and more preferably (i). In the embodiment (i), when a fluid other than the slurry liquid is flowed, the pressure of the fluid may be, for example, 0.01 MPa to 0.5 MPa.

[0053] After the jig is passed through the tube of the substrate, a fluid such as air may be passed through the tube to hold the tube in a pressurized state for a certain period of time, and in this way, the solvent, thickener, etc. in the slurry can be discharged to the outside of the tube through the pores of the substrate. The pressurizing pressure is, for example, 0.01 MPa to 0.5 MPa, and the holding time is, for example, 1 minute to 30 minutes.

[0054] The material of the jig is not particularly limited, and a jig made of resin, metal, ceramic, or the like can be used. The shape of the jig is preferably such that when projected in the moving direction of the jig inside the pipe, at least a part of the outer periphery of the projection is curved, specifically, a coil shape, a cylindrical shape, an elliptical cylindrical shape, a cone shape, a spherical shape, and a shape combining these shapes can be mentioned. In addition, among these shapes, a shape other than a coil shape is preferably cut with one or more planes parallel to the moving direction of the jig, and a part of the outer periphery is removed while leaving a part of it, and the jig may be moved inside the pipe while rotating. The shape of the jig is preferably such that the inner periphery shape of the cross section perpendicular to the axial direction of the pipe is a circle, specifically, a cylinder or a sphere, and a sphere is more preferable. The size of the jig may be appropriately adjusted according to the thickness of the ceramic porous layer to be formed within a range that can be inserted inside the pipe.

[0055] After forming a coating layer of the slurry liquid on the inner surface of the pipe using a jig, a drying step (3) is usually carried out to dry the coating. Drying is preferably performed by air-drying the coating layer, and the temperature of the air blown onto the coating may be room temperature or may be hot air in the range of 100° C. or less. The speed of the air blown onto the coating surface is, for example, 0.05 m / sec to 1 m / sec.

[0056] After the drying step (3), a heat treatment step (4) is preferably carried out. The heat treatment promotes sintering of particles (preferably inorganic oxides) contained in the slurry liquid, and can improve the strength of the layer formed from the slurry liquid and appropriately adjust the porosity. The heat treatment is preferably carried out at, for example, 300°C to 1500°C. The heat treatment time is, for example, 30 minutes to 10 hours.

[0057] The thickness of the ceramic porous layer formed on the tube inner surface of the substrate may be adjusted by, for example, adjusting the viscosity of the slurry liquid; performing a series of steps including the slurry liquid supply step (1) and the slurry liquid coating layer formation step (2) (and, if necessary, the drying step (3) and the heat treatment step (4)) two or more times; adjusting the particle concentration in the slurry; or adjusting the size of the jig.

[0058] (4) Separation membrane The porous ceramic laminate of the present invention can be used as a microfiltration membrane, an ultrafiltration membrane, or a nanofiltration membrane, and can be further laminated with a functional layer as necessary to be used as a microfiltration membrane, an ultrafiltration membrane, a nanofiltration membrane, a reverse osmosis membrane, an ion exchange membrane, a separation membrane for gas, etc. In the separation membrane, it is preferable that a functional layer is provided on the outermost surface of the porous ceramic laminate of the present invention opposite to the first porous ceramic layer.

[0059] Examples of the functional layer include zeolite, MOF (Metal Organic Frameworks), porous silica membrane, and porous alumina membrane. A separation membrane equipped with a functional layer can be produced by applying a liquid containing inorganic particles or MOF that constitute the functional layer and reacting it. The synthesis conditions can be appropriately selected depending on the functional layer to be laminated, and may be, for example, 80°C to 800°C for 1 hour to 72 hours. EXAMPLES

[0060] The present invention will be described in more detail below with reference to examples. The present invention is not limited to the following examples, and can of course be modified within the scope of the above and below-mentioned aims, and all such modifications are within the technical scope of the present invention.

[0061] [Method of measuring the number of branch points] Three-dimensional observation was performed using an X-CT (Nano-CT, manufactured by Rigaku Corporation) so that the area from the surface corresponding to the inner circumference of each of the following substrates A to D, which are the first porous ceramic layers, to about 600 μm inside could be observed. The observation conditions were as follows: Mo target, tube voltage = 50 kV, tube current = 24 mA, camera length XD = 3 mm, exposure time = 30 s, FOV = 0.65 mm × 0.65 mm, resolution = 0.32 μm / voxel, number of images = 1200, rotation range = 0° to 180°, and StepScan mode. Using the captured image, noise and ring removal operations are performed using reconstruction software (nano3DX Reconstruction; Rigaku Corporation) to obtain a 3D model of the porous base material layer. The image resolution is X, Y, Z = 0.32 μm / pix. The obtained 3D model is trimmed to a size of 350 μm × 350 μm × 350 μm, and a 3D quantitative analysis of the voids in the base layer is performed. For the 3D quantitative analysis, quantitative analysis software TRI / 3D-BON-FCS (manufactured by Ratoc Systems Engineering) is used. Specifically, open the above software, convert the image into two gradations using Auto-LW, and identify the trabecular bone and pores (voids) that make up the porous layer. If the above two gradations are insufficient or excessive, use the image calculation function to extract them appropriately. For the voids identified by these processes, a structural analysis was performed using 3D cancellous bone measurement with the software's bone measurement option, with the analysis direction set to the direction in which the outer peripheral surface of the base material is observed parallel, MIL effective length = 0.5 x Thickness, NdNd effective length = 1.5 x Thickness, and NdTm effective length = 2.0 x Thickness. The number of connection points (bonding points) Nd in the voids of the porous layer, that is, N.Nd = the number of branching points (pieces), which indicates how many branches the voids have, and TV (μm), which is the total volume of the trabecular bone and voids (i.e. the volume of the entire analysis area), were calculated. 3 ) and calculate the number of branches per unit volume, N. Nd / TV. The number of branching points indicates how many branching points the voids have, so a large value indicates that there are many paths through which the voids can pass.

[0062] [Measurement of pore diameter] The pore diameter D50 of the first porous ceramic layer was determined by the software from the average value of the length between the connection points (bonding points) Nd of the voids in the porous layer obtained by the three-dimensional analysis and the width of the voids.

[0063] [Metal oxide particle size measurement] The particle size distribution of the alumina used in the examples and comparative examples was measured using a laser diffraction / scattering particle size distribution measuring device (Microtrac MT3300EX II, 0.2 mass% aqueous solution of sodium hexametaphosphate, manufactured by Microtrac Corporation), and the volume-based cumulative 50% equivalent diameter was measured.

[0064] [Cross-section observation of laminate] The cylindrical porous ceramic laminate obtained in the examples was cut in a cross section perpendicular to the axial direction, embedded in resin so that the cut surface could be observed, and mechanically polished. Platinum was vapor-deposited on the polished surface, and the cross section was observed and photographed at 1000x magnification using a FE-SEM (JSM-7500FA (manufactured by JEOL). The perimeter of the particles observed in the obtained SEM image was determined, and the particle was considered to be a circle with that perimeter, and the diameter of the particle was calculated to be the equivalent circle particle diameter of the particle. From the obtained equivalent circle particle diameter, the presence of large and small particles was confirmed. The equivalent circle particle diameter of the small particles was measured by enlarging it to a degree where the equivalent circle particle diameter could be confirmed (for example, 20,000x).

[0065] [Average circle equivalent particle size of large particles present on the surface of the first porous ceramic layer] In the SEM image of the cross section of the laminate, 20 large particles were arbitrarily selected from the portion between the lines X1 and X0 shown below, and the average circle-equivalent particle diameter of the large particles was calculated. Line X1: A line that contacts the first porous ceramic layer at two or more points and does not cross the first porous ceramic layer. Straight line X0: A line parallel to the straight line X1 and spaced 10 μm apart in the direction toward the inside of the first porous ceramic layer

[0066] [Method for measuring the volume of protruding valleys and peaks] Three-dimensional observation was carried out using a laser microscope (VK-X3000, manufactured by Keyence Corporation) so that the surfaces corresponding to the inner peripheries of the below-mentioned base materials A to D, which are the first porous ceramic layers, could be observed. The observation was performed using software for the laser microscope (Keyence Corporation: VK-X3000 Observation Application Ver2.3.0.151). The observation conditions were as follows: in the measurement settings, measurement mode = surface profile, scan mode = laser confocal, measurement size = standard, pitch = 2.00um, RPD = ON, average number = 1, optical zoom = 1.0x, Z-axis mode = recommended settings. In the head, head = V, objective lens name = Plan, objective lens magnification = 10X, NA = 0.3, field curvature correction = ON, light intensity decentering correction = ON. In the laser settings, received light intensity correction mode = gamma correction, gamma coefficient = 0.45, offset = 0%. Using the captured image data, correction was performed using analysis software (Keyence Corporation: VK-X3000 Multi-File Analysis Application Ver. 3.3.185) to calculate the volume of the protruding valleys and the volume of the protruding peaks. The correction was performed with height cut level = medium, surface shape correction = cylindrical correction, and surface shape correction = waviness removal (strength: 5). The settings for calculation were filter type = Gaussian, S-filter (low-pass filter) = none, F-operation (shape correction) = none, L-filter (high-pass filter) = none, and end effect correction: ON.

[0067] Example 1 (base material) A commercially available substrate A was used as the first porous ceramic layer. Substrate A contains Al as the main raw material, as well as Si, O, etc., and is cylindrical with an inner diameter of 7.0 mm, an outer diameter of 9.5 mm, and a length of 10 cm. The pore diameter D50 is 15.4 μm, and the number of branch points per unit volume of the pores measured by the above method is 1.71 × 10 6 pieces / μm 3 It was.

[0068] (Preparation of Slurry S1) Alumina powder AA-10 manufactured by Sumitomo Chemical Co., Ltd. (cumulative 50% equivalent diameter on a volume basis is approximately 14.8 μm), hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 (active ingredient 41%) as a dispersant were mixed with water to concentrations of 10 mass%, 1.5 mass%, and 1 mass%, respectively, to prepare slurry S1.

[0069] (Formation of porous ceramic layer 1) The slurry S1 was filled into a catheter syringe manufactured by Terumo Corporation, and the syringe was left standing for 1 hour with the outlet facing downward. A tube was attached to the tip of the catheter syringe manufactured by Terumo Corporation, and the tip of the tube was connected to one end of the vertically placed substrate A (hereinafter referred to as end A; the other end opposite end A is referred to as end B) with the end facing downward, and the slurry S1 was injected onto the entire inner circumferential surface of the substrate.

[0070] After injecting the slurry S1, a resin ball X with a diameter of 6.7 mm was set at the end B (upper end side) of the substrate, and the slurry S1 was discharged by moving the ball from the end B to the end A by flowing air at an air pressure of 0.1 MPa from the end B, and then the ball was held at the end A and maintained at 0.1 MPa for 30 s. Thereafter, the substrate A was rotated at 6.9 rpm, and hot air of about 0.1 m / s was blown through the inside of the substrate A to dry it. Thereafter, the substrate A with the slurry S1 applied to the inner surface thereof was heat-treated at 1200° C. for 3 hours, and a layer containing AA-10 particles was formed on the inner surface of the substrate A.

[0071] (Preparation of Slurry S2) Next, alumina powder AKP-20 manufactured by Sumitomo Chemical Co., Ltd. (having a cumulative 50% equivalent diameter on a volume basis of approximately 0.42 μm), hydroxypropyl methylcellulose 65SH-30000 manufactured by Shin-Etsu Chemical Co., Ltd. as a thickener, and SN Dispersant 5468 as a dispersant were mixed in water at concentrations of 9 mass%, 1.5 mass%, and 1 mass%, respectively, to prepare a slurry S2.

[0072] (Formation of porous ceramic layer 2) The slurry S2 was filled into a catheter syringe manufactured by Terumo Corp., and the syringe was left standing for 1 hour with the outlet facing downward. A tube was attached to the tip of the catheter syringe manufactured by Terumo Corp., and the tip of the tube was connected to the end A of the substrate having a layer containing AA-10 particles formed on the inner surface thereof, which was placed vertically, with the end A facing downward, and the slurry S2 was injected into the entire inside of the substrate.

[0073] After injecting the slurry S2, a ball Y having a diameter of 6.35 mm was set at the end B of the slurry of the base material, and air was flowed from the end B at an air pressure of 0.02 MPa to move the ball from the end B to the end A, thereby discharging the slurry. The base material was rotated at 6.9 rpm, and hot air of about 0.1 m / s was blown through the inner surface of the base material to dry it, forming a layer containing AKP-20 on the layer containing AA-10 particles (an intermediate layer, which also contains AKP-20 of the slurry S2). The base material having a layer containing AA-10 particles and a layer containing AKP-20 formed on the inner surface was heat-treated at 1200 ° C. for 3 hours.

[0074] After the heat treatment, the slurry S2 was applied again. The application process was the same as the first application process of the slurry S2, except that a ball was set at the end A (upper end side) of the substrate, air was flowed from the end A to discharge the slurry, and a ball Y having a diameter of 6.35 mm was used. After the application process, a heat treatment process was performed at 1200°C for 3 hours.

[0075] Example 2 The first porous ceramic layer contains Al as the main raw material, and also contains Si, O, etc., and has a cylindrical shape with an inner diameter of 6.6 mm, an outer diameter of 10.0 mm, and a length of 10 cm. The pore diameter D50 is 14.4 μm, and the number of branch points per unit volume of the pores is 1.26 × 10 6 pieces / μm 3A porous ceramic laminate of Example 2 was obtained in the same manner as in Example 1, except that a commercially available substrate B was used, the diameter of the ball X used in applying the slurry S1 and the first application of the slurry S2 was changed from 6.7 mm to 6.35 mm, and the diameter of the ball Y used in applying the slurry S2 for the second time was changed from 6.35 mm to 6.0 mm.

[0076] Comparative Example 1 The first porous ceramic layer contains Al as the main raw material, and also contains Si, O, etc., and is cylindrical with an inner diameter of 6.0 mm, an outer diameter of 9.9 mm, and a length of 10 cm. The pore diameter D50 is 12.8 μm, and the number of branch points per unit volume of the pores is 8.49 × 10 5 pieces / μm 3 A porous ceramic laminate of Comparative Example 1 was obtained in the same manner as in Example 1, except that a commercially available substrate C was used, the diameter of ball X was changed from 6.7 mm to 5.5 mm, and the diameter of ball Y was changed from 6.35 mm to 5.0 mm.

[0077] Comparative Example 2 The first porous ceramic layer contains Al as the main raw material, and also contains Si, O, etc., and has a cylindrical shape with an inner diameter of 6.9 mm, an outer diameter of 10.5 mm, and a length of 10 cm. The pore diameter D50 is 13.0 μm, and the number of branch points per unit volume of the pores is 7.89 × 10 5 pieces / μm 3 A porous ceramic laminate of Comparative Example 2 was obtained in the same manner as in Example 1, except that a commercially available substrate D was used, the diameter of ball X was changed from 6.7 mm to 6.35 mm, and the diameter of ball Y was changed from 6.35 mm to 6.0 mm.

[0078] [Peel strength test] The porous ceramic laminates obtained in the examples and comparative examples were evaluated according to JIS K5600 General Test Method for Paint Scratch Hardness (Pencil Method) 5-4. A pencil hardness tester (Yasuda Seiki Seisakusho Co., Ltd. 533-M1, weight: 750g, pencil moving speed: 1mm / sec) was used to draw a line on the surface of the laminate (the surface opposite to the first porous ceramic layer) with a soft pencil (Mitsubishi Pencil Co., Ltd.: Mitsubishi Uniseries 6B-9H), and the surface was observed using a digital microscope (Keyence Corporation: VHX-5000), and the hardness just before the hardness at which peeling, dents, or scratches were observed was evaluated as the hardness of the sample. The results are shown in Table 1.

[0079] [Table 1]

[0080] As can be seen from the inner diameter of the substrate and the size of the ball used, the comparative example has a thicker film thickness of the other porous ceramic layer formed on the substrate compared to the example, and since the film strength is improved, it is normally expected that the peel strength will be improved. However, in the comparative example, the number of branching points of the pores in the substrate does not meet the requirements of the present invention, and as a result, the peel strength was inferior despite the film thickness of the other porous ceramic layer being thicker than in the example.

[0081] Fig. 4 shows a cross-sectional view of the laminate obtained using the substrate of Example 1. As shown in Fig. 4, a layer containing small particles having a circle-equivalent particle diameter of less than 1 µm was laminated on the first porous ceramic layer, and the small particles and large particles having a circle-equivalent particle diameter of 2 µm to 25 µm were present on the surface of the first porous ceramic layer on the side of the layer containing the small particles, and the layer containing the small particles was composed of an outer layer containing small particles and not containing the large particles, and an intermediate layer containing both the small particles and the large particles. [Explanation of symbols]

[0082] 11. Turning Point 21, 31 First porous ceramic layer 22, 32, 33 Other porous ceramic layers

Claims

1. A porous ceramic laminate in which one or more other porous ceramic layers are laminated on a first porous ceramic layer composed of ceramic trabeculae and pores, The number of branching points of the pores is within 1 μm of the total volume of the ceramic trabecula and the pores. 3 1.0 x 10 per 6 The porous ceramic laminate has at least one porous ceramic layer.

2. The volume of the protruding valley of the first porous ceramic layer surface, as determined according to ISO 25178, is 0.56 ml / m 2 The porous ceramic laminate according to claim 1, wherein the porous ceramic laminate has a thickness of more than 100 nm.

3. 3. The porous ceramic laminate according to claim 1, wherein the other porous ceramic layer is composed of two or more layers.

4. the other porous ceramic layer is a layer containing small particles having a circle-equivalent particle diameter of less than 1 μm in a cross section parallel to the stacking direction of the laminate, A porous ceramic laminate as described in claim 1 or 2, wherein the small particles and large particles having a circle equivalent particle diameter of 2 μm to 25 μm are present on the surface of the first porous ceramic layer facing the other porous ceramic layer.

5. 5. The porous ceramic laminate according to claim 4, wherein the layer containing the small particles comprises an outer layer containing the small particles but not the large particles, and an intermediate layer containing both the small particles and the large particles.

6. The average circle-equivalent particle diameter of the large particles present on the surface of the first porous ceramic layer is equal to or smaller than the average pore diameter D of the first porous ceramic layer. 50 5. The porous ceramic laminate according to claim 4, wherein the average particle diameter is 0.3 times or more.

7. 5. The porous ceramic laminate according to claim 4, wherein said large particles and said small particles are both made of an inorganic oxide.

8. 3. The porous ceramic laminate according to claim 1, which is in the form of a tube or a monolith.

9. A separation membrane comprising the porous ceramic laminate according to claim 1 or 2.

Citation Information

Patent Citations

  • Alumina porous material and production method of the same

    JP2010228946A

  • Alumina porous body and method of producing the same

    JP2010228948A

Cited By

  • Porous ceramic layer for separation membrane, porous ceramic laminate for separation membrane, and separation membrane

    WO2026191994A1